Markets and Jungles - Thomas Gall; Paolo Masella (Verein für Socialpolitik, 2010)
Economic institutions determine prospects for growth and development. In this paper a condition on the primitives determines whether an economy supports institutions that implement markets. Agents differ in land holdings, skill, and power. A competitive market assigns land to the skilled, not necessarily to the powerful. Therefore a market allocation needs to be robust to coalitional expropriation. More equally distributed power and higher congruence of land and power favor stable markets. Whether markets are stable forever in a dynamic setting, or alternate with expropriation in a limit cycle, decreasing efficiency and amplifying macroeconomic fluctuations, depends on social mobility, initial inequality, and the mismatch between demand and supply.
Keywords: E00; O40; C71; 330; Expropriation; market institutions; inequality; fluctuations; coalition formation